Taxonomy of European Damaeidae (Acari: Oribatida) IV. Partial revision of Metabelba Grandjean, 1936 with proposal of one new subgenus, one new species and redescriptions of two known species - Mourek, Jan; Miko, Ladislav; Bernini, Fabio (Zootaxa, 2011)
We review the current state of taxonomy of the oribatid mite genus Metabelba Grandjean, 1936 (Damaeidae) and present an amended generic diagnosis. In contrast to Subías (2004) we consider Allobelba Kunst, 1961 and Neobelba BulanovaZachvatkina, 1967 as separate genera, not subgenera of Metabelba. We consider the subgenus Metabelba (Parametabel- ba) Mihelčič, 1964, to be a nomen nudum and propose a new subgenus—Metabelba (Pateribelba) n. subg., with type species Metabelba (Pateribelba) sphagni Strenzke, 1950—to replace it. Pateribelba n. subg. includes species of Metabelba without the propodolateral apophysis. Together with the type species, the following named species (new combinations) belong to this subgenus: Metabelba (Pateribelba) italica (Sellnick, 1931); M. (P.) romandiolae (Sellnick, 1943); M. (P.) platynotus Grandjean, 1954; M. (P.) ericius Kunst, 1957; M. (P.) rhodopeia Kunst, 1961; M. (P.) filippovi Bulanova-Zachvatkina, 1965; M. (P.) flagelliseta Bulanova-Zachvatkina, 1965; M. (P.) monilipeda Bulanova-Zachvatkina, 1965; M. (P.) pseudoitalica Bulanova-Zachvatkina, 1965; M. (P.) paraitalica Kulijev, 1967, M. (P.) glabriseta Mahunka, 1982 and M. (P.) machadoi Pérez-Iñigo, 1986. A new species Metabelba (Pateribelba) denscanis n. sp. is described and illustrated; it is characterized mainly by the presence of a notogastral cornicle in the adult. It was found in Central Bohemia (Czech Republic), Upper Silesia (Poland) and South Tyrol (Italy). Metabelba romandiolae and M. sphagni are redescribed and illustrated. Metabelba gladiator Mihelčič, 1963 is considered to be junior synonym of M. romandiolae. Metabelba lanceolata van der Hammen, 1952 is considered to be a junior synonym of M. sphagni. We also provide a ten-tative diagnostic key of the known species of Metabelba (Pateribelba) n. subg., based on detailed study of available species and a review of literature data.